2023
DOI: 10.1002/pc.27496
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive self‐healing design for carbon fiber/epoxy composites

Abstract: Self‐healing composites are promising for engineering, but self‐healing structures or components usually induce reduction in the composite's mechanical properties. In this paper, core‐shell nanofibers which accommodating healing agent in the core and incorporating carbon nanotubes (CNTs) in the shell were produced to develop non‐destructive self‐healing carbon fiber/epoxy (CF/EP) composites. The epoxy resin and curing agent were encapsulated in CNTs‐reinforced polyacrylonitrile (PAN) core‐shell electrospinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Different stacking configurations were employed for that purpose to report the highest recovery rate of 80% of the pre‐impact flexural strength 14 . In a similar vein, Wan et al confirmed the self‐healing capacity of CNT reinforced core–shell electrospun nanofibre interleaved composites 15 . A recovery rate of 93.5% was reported at an optimum 1 wt% concentration of CNT under flexural loading.…”
Section: Introductionmentioning
confidence: 74%
“…Different stacking configurations were employed for that purpose to report the highest recovery rate of 80% of the pre‐impact flexural strength 14 . In a similar vein, Wan et al confirmed the self‐healing capacity of CNT reinforced core–shell electrospun nanofibre interleaved composites 15 . A recovery rate of 93.5% was reported at an optimum 1 wt% concentration of CNT under flexural loading.…”
Section: Introductionmentioning
confidence: 74%
“…Where CNTs can improve the electrical conductivity of composites, and the incorporation of CNTs in the shell of nanofibers enhances the self-healing and mechanical properties. 25 Tensile and flexural tests were conducted to evaluate the composite under different failure modes, and real-time resistance changes were collected and analyzed for in-situ damage monitoring. Furthermore, cyclic three-point bending experiments were performed on composites to evaluate the self-healing properties, and the damaged specimens were subjected to resistive heating during the healing process to expedite the healing process.…”
Section: Introductionmentioning
confidence: 99%
“…After five cycles of bending tests, the residual bending strength of the samples still reached 75% of the original strength. Similarly, Wan et al 35 added carbon nanotubes (CNTs) into PAN core–shell nanofibers, and the flexural strength of the composites containing 1 wt% CNTs increased by 10% compared to the specimens without CNTs. Furthermore, the bending strength recovered to 93.57% after the first repair.…”
Section: Introductionmentioning
confidence: 99%